Estrogens Recent Advances - Marsh, Courtney (IntechOpen, 2023)
Estrogen - Recent Advances explores the role of estrogen in many disease processes and organ systems. Chapters discuss G-protein estrogen receptor signaling and estrogen's effect on the oral cavity, olfactory mucosae, and the prostate. The book presents cutting-edge research and developments in the field. Understanding the many effects estrogen has on the body will help the reader better understand disease processes and provide a framework for future discoveries.